Low Dose-Rate Irradiation of Gamma-Rays-Induced Cytotoxic and Genotoxic Alterations in Peripheral Erythrocytes of p53-Deficient Medaka (Oryzias latipes) - Sayed, Alaa El-Din H.; Nagata, Kento; Nakazawa, Takuya; Mitani, Hiroshi; Kobayashi, Junya; Oda, Shoji (Frontiers in Marine Science, 2021)
Morphological alterations and nuclear abnormalities in fish erythrocytes have been used in many studies as bioindicators of environmental mutagens including ionizing radiation. In this study, adult Japanese medaka (Oryzias latipes) were irradiated with gamma rays at a low dose rate (9.92 μGy/min) for 7 days, giving a total dose of 100 mGy; and morphological alterations, nuclear abnormalities, and apoptotic cell death induced in peripheral erythrocytes were investigated 8 h and 7 days after the end of the irradiation. A variety of abnormalities, such as tear-drop cell, crenated cell, acanthocyte, sickled cell, micronucleated cell, eccentric nucleus, notched nucleus, and schistocyte, were induced in the peripheral erythrocytes of the wild-type fish, and a less number of abnormalities and apoptotic cell death were induced in the p53-deficient fish. These results indicate that low dose-rate chronic irradiation of gamma rays can induce cytotoxic and genotoxic effects in the peripheral erythrocytes of medaka, and p53-deficient medaka are tolerant to the gamma-ray irradiation than the wild type on the surface.